The Multicultural Islamic Education Development Strategy on Educational Institutions - Hifza Hifza; Antoni Antoni; Abdul Wahab Syakhrani; Zainap Hartati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The aim of this study was to analyse the strategies for the development of multicultural Islamic education in Islamic educational institutions. It used literature studies based on a qualitative approach. The study showed that: the first the foundation of multicultural Islamic Education Development consists of religious, historical, psychological, sosio-kultural and geographic foundations. Second, the Multicultural Islamic Education development strategy on Islamic educational institutions can be pursued through two approaches, namely quantitative and qualitative. Quantitative development strategy was with the socialization and internalization program through scientific activities, multicultural education innovation programs, and build a culture that accommodates the spirit and multicultural values in the environment of Islamic institutions. While the development strategy qualitative was the intensive study program of the Qur'an and Sunnah, curriculum revision programs, education and training programs for educators, and local wisdom programs. Keywords: Development Strategy, Multicultural Islamic Education, Strategy Educational Institution